Synergistic regulation of gut microbiota and metabolites by breast milk and probiotics in the prevention of neonatal necrotizing enterocolitis: mechanisms and prospects - Chen, Siyi; Li, Jiahong; Zhang, Le (Translational Pediatrics, 2026)
Necrotizing enterocolitis (NEC) remains one of the most devastating gastrointestinal emergencies in preterm infants and is associated with high morbidity, mortality, and long-term complications. Increasing evidence suggests that breast milk and probiotics may act synergistically to reduce NEC risk by modulating the intestinal microbiota, its metabolites, and host immune responses. As the optimal nutritional source for preterm infants, breast milk provides a wide range of bioactive components, including human milk oligosaccharides (HMOs), lactoferrin, and immunoglobulins, which promote intestinal maturation, strengthen epithelial barrier function, inhibit pathogen colonization, and support immune development. Probiotics further complement these protective effects by enhancing the colonization of beneficial bacteria, suppressing the overgrowth of potential pathogens, improving barrier integrity, and regulating inflammatory signaling. In this context, microbial metabolites emerge as critical proximal mediators linking microbial composition to host protection. Among them, short-chain fatty acids (SCFAs) and tryptophan-derived indole metabolites play essential roles in maintaining intestinal homeostasis, promoting mucosal integrity, and modulating immune tolerance. Therefore, the preventive effects of breast milk and probiotics should be understood not only as independent benefits, but also as coordinated ecological and metabolic regulation of the immature gut. A better understanding of these interactions may provide a mechanistic basis for developing personalized and evidence-based strategies for NEC prevention in preterm infants.